Recommendations for the Diagnosis and Treatment of Maternal SARS-CoV-2 Infection. Issue 2 (28th April 2023) - Chen, Dunjin; Dai, Yue; Liu, Xinghui; Qi, Hongbo; Wang, Chen; Wang, Lan; Wei, Yuan; Xu, Xiaochao; Zhang, Chuan; Zhang, Lingli; Zhang, Yuquan; Zhao, Ruihua; et al.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has spread worldwide and threatened human's health. With the passing of time, the epidemiology of coronavirus disease 2019 evolves and the knowledge of SARS-CoV-2 infection accumulates. To further improve the scientific and standardized diagnosis and treatment of maternal SARS-CoV-2 infection in China, the Chinese Society of Perinatal Medicine of Chinese Medical Association commissioned leading experts to develop the Recommendations for the Diagnosis and Treatment of Maternal SARS-CoV-2 Infection under the guidance of the Maternal and Child Health Department of the National Health Commission. This recommendations includes the epidemiology, diagnosis, management, maternal care, medication treatment, care of birth and newborns, and psychological support associated with maternal SARS-CoV-2 infection. It is hoped that the recommendations will effectively help the clinical management of maternal SARS-CoV-2 infection.